Fragmented Ethics of Gen Z in the Age of Digital Disruption - Anisa Rizki Sabrina; Ratna Triwurian Danu; Fairuza Arindra (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2026)
Digital disruption has fundamentally transformed how Generation Z communicates, yet little scholarly attention has been paid to how this generation constructs and negotiates ethical boundaries within everyday online interactions. Grounded in Erving Goffman's Dramaturgical Theory and Social Identity Theory, this study examines the reconfiguration of ethical values in Gen Z's digital communication practices across TikTok, Instagram, and Twitter/X. Employing a qualitative netnographic approach combined with summative content analysis, data were gathered from February to June 2025 through digital ethnography of selected accounts demonstrating key phenomena of alter account use, generational slang, and platform-specific ethical norms. The analysis reveals that Gen Z exhibits a highly contextual and performative mode of ethical reasoning, wherein alter accounts reflect Goffman's front stage and back stage dynamics and the adoption of exclusive slang signals in-group solidarity consistent with Social Identity Theory. Rather than adhering to fixed normative codes, Gen Z constructs ethics through community consensus, algorithmic visibility, and affective engagement. These findings suggest that digital disruption does not merely alter media channels but actively reshapes generational ethics into dynamic, situational, and socially negotiated constructs — with practical implications for digital literacy education, content regulation, and intergenerational communication strategy.